Transport, Persistence and Toxicity of Pollutants in the Sea - Marini, Mauro; Annibaldi, Anna (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint describes the fate of pollutants transported to the sea from the mainland and how they accumulate in the marine environment and organisms. This will contribute to increasing the knowledge on the dangers of pollutants that reach the marine environment and their fate once they enter the marine food chain. We also hope to improve knowledge on the effects of the pollutant load on the sea during all the seasons, due to the contribution of rivers, rainfall, etc., and the relative influence on marine organisms.